(untitled) (Vietnam Journal of Community Medicine, 2024)
Airway management of the patient maxillectomy with free flap reconstruction is unique challenges for anesthetic. To ensure safety, a clear strategy, collaborative approach and effect is essential. Maxillofacial cancer causes major changes in the anatomy of the upper respiratory, making it difficult to intubation and extubation. In particular, extubation is difficult, risks and complications. Tracheostomy is often chosen after major maxillofacial cancer sugery. However, tracheostomy also has many risks: swallowing function, tracheal stenosis… affects quality of life. Also, consider between tracheostomy immediately after surgery and delaying, evaluating extubation when qualified, to avoid tracheostomy. This is a case of difficult intubation and extubation in the patient with maxillofacial cancer at the Department of Anesthesiology 2, Viet Duc Unisversity Hospital.